(untitled) (Marketing Journal, 2025)
This article analyzes the impact of profit tax collected from commercial banks on the formation of state budget revenues of the Republic of Uzbekistan. Based on statistical data for 2010 –2024, the dynamics of the tax share, forecast indicators, and factors of economic efficiency are studied. According to the research results, the role of bank profit tax in financial stability of the state, diversification of budget revenues, and improvement of tax policy is scientifically substantiated.